Perioperative use of anticoagulant and antiaggregant drugs; approaches of anesthesiology and reanimation physicians in Türkiye: A survey study - Eman, Ali; Balaban, Onur (Annals of Medical Research, 2022)
Aim: We aimed to assess the approach of Turkish Anesthesiology and Reanimation Specialists in patients receiving preoperative anticoagulant/antiaggregant therapy. A survey was designed to evaluate perioperative management of anticoagulant/antiaggregant drugs. Materials and Methods: We surveyed Anesthesiology and Reanimation specialists and residents in various hospitals in Türkiye through e-mail and smartphone messenger application. We asked them to complete questionnaire form regarding anticoagulant use on a voluntary basis between February 15 and March 15 in 2022. Results: The survey was responded by 296 anesthesiology specialists and residents. The majority of the participants (73.3%) were anesthesiology specialist physicians and work in 3rd level (academic, teaching, or university) hospital. The mostly used antithrombotic drugs were warfarin (75.9%) and acetylsalicylic acid (100%). Most of the participants (61%) use international guidelines regarding the timing of drug discontinuation. Participants commonly (82%) refer to the consultant specialist of the patient for deciding to discontinue or restarting the patient’s antithrombotic drug. The major perioperative concern about the antithrombotic drugs was bleeding complications of central neuraxial procedures (44.8%). Conclusion: The anesthesia and reanimation specialists in Türkiye manage antithrombotic drugs in accordance with international guidelines. The distribution ranges are wide in times of preoperative discontinuation and postoperative restarting times of the medications; thus, the awareness needs to be increased to clear up this controversy.